Using newspapers in the classroom - Sanderson, Paul. (Cambridge, U.K. New York : Cambridge University Press, 1999)
Using Newspapers in the Classroom is a collection of over 130 practical and creative newspaper-based activities to use with young adult and adult learners from pre-intermediate to advanced levels. The activities, which show teachers how to exploit the different features and sections of newspapers, are designed to provide motivating and challenging learning experiences, as well as valuable language practice. Clear lesson plans, sample materials and practical guidelines combine to give teachers of general English and English for specific purposes maximum support for using newspapers in the classroom.
Includes bibliographical references
Keywords: Newspapers in education; Language arts